PENGARUH PENGALAMAN KERJA, PELATIHAN, DAN PENGELOLAAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP SURAKARTA - Pratiwi, Dias Bella; Widiastuti, Erni (Universitas Of Surakarta, 2022)
This study aims to determine the effect of the influence of work experience, training, and quality management of human resources on employee performance either partially or simultaniously. This research is a quantitative research which collects data using questionnaires and uses 94 respondents as the research sample. The analysis technique that used in this research are multiple linear regression, t test (partial), F test (simultaneous), and coefficients of determination ( ). Based on the analytical technique can be concluded that work experience, training, and human resource quality management and either partiall or simultaneiously have a positive and significant effect on employee performance.